Strategy for Sustainable Hydropower Development in the Jhelum Poonch River Basin Pakistan (Energy Study, 2021)
IFC has remained financer and development partner in hydropower projects in Pakistan. In this process, IFC has developed a comprehensive approach for developing sustainable hydropower as a cheaper and cleaner energy that benefits the environment as well as the communities in the area. A key part of the approach involves raising environmental and social standards in hydropower development through its advisory engagements. Strategy for Sustainable Hydropower Development in the Jhelum Poonch River Basin (JPRB) is one such IFC initiative implemented through a multistakeholder-engagement process to provide practical guidance for government, developers, and other stakeholders. The proposed strategy presents key lessons learned from hydropower projects in the Jhelum-Poonch River Basin as well as other related basins during construction and operation. It enhances the knowledge base of the Jhelum-Poonch Basin and provides recommendations for hydropower developers and government to implement best practice in their projects. This helps strike a balance between conservation and development by minimizing negative environmental and social impacts from hydropower projects in the basin. The strategy provides recommendations for government and regulators on how to improve policy and regulation to strengthen the hydropower sector. Developers can make good use of this report to strengthen their planning, systems, and business operations